2015
DOI: 10.1186/s12913-015-1029-3
|View full text |Cite
|
Sign up to set email alerts
|

Medication reviews are useful, but the model needs to be changed: Perspectives of Aboriginal Health Service health professionals on Home Medicines Reviews

Abstract: BackgroundThe Australian Home Medicines Review (HMR) program consists of a pharmacist reviewing a patient’s medicines at his or her home and reporting findings to the patient’s general practitioner (GP) to assist optimisation of medicine management. Previous research has shown that the complex HMR program rules impede access to the HMR program by Aboriginal and Torres Strait Islander clients.This study explores the attitudes and perceptions of health professional employees working within Aboriginal Health Serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…HMRs can only be initiated by a GP. There is a low HMR participation rate from GPs and a poor awareness among patients . Low GP participation has been reported to relate to the cumbersome consent, referral and implementation processes, and inconsistent quality of service provided by pharmacists .…”
Section: What Is Known and Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…HMRs can only be initiated by a GP. There is a low HMR participation rate from GPs and a poor awareness among patients . Low GP participation has been reported to relate to the cumbersome consent, referral and implementation processes, and inconsistent quality of service provided by pharmacists .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…There is a low HMR participation rate from GPs and a poor awareness among patients. 14,[17][18][19][20][21] Low GP participation has been reported to relate to the cumbersome consent, referral and implementation processes, and inconsistent quality of service provided by pharmacists. 18,19 Attempts to increase HMR uptake, including for home nursing clients, have been unsuccessful.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…These reviews are aimed at enhancing the quality use of medicines and reducing the number of adverse drug events experienced by consumers. A Home Medicines Review is designed to enhance the quality use of medicines and reduce the number of adverse medicine events by assisting consumers to better manage and understand their medicines through a medication review conducted by an accredited pharmacist in the patient's home (http://www.6cpa.com.au/medication-management-programs) at a lower rate than non-Indigenous Australian for reasons including the lack of culturally responsive services, not having established and trusting relationships with pharmacists and because pharmacists are not usually integrated into AHSs 16 17…”
Section: Discussionmentioning
confidence: 99%
“…The IMeRSe intervention is delivered by local community pharmacists (on a fee-for-service basis) integrated with local Aboriginal health services (AHSs). Previous research has shown that Indigenous people encounter barriers to accessing medication review services,16 17 thus the aim of IMeRSe is to overcome these barriers and meet the health needs of the population 15…”
Section: Introductionmentioning
confidence: 99%
“…37 More recently, there have been calls for pharmacists to play an integral role within AHS, particularly in the delivery of Home Medication Reviews. 37 Being more closely involved with the AHS would enable pharmacists to attain appropriate education in the cultural sensitivities required to reduce barriers to delivery of such an important service in medication management 38 , 39 and may provide a catalyst that would potentially be of benefit to such a co-ordinated approach.…”
Section: Discussionmentioning
confidence: 99%